The effect of asymmetric information and financial distress ratio on earnings management with corporate governance as moderating variables - Sanchia Fairuz Salsabil; Dwi Marlina Wijayanti (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2024)
This study aims to examine the effect of asymmetric information and financial distress ratio on earnings management with corporate governance as a moderating variable. Previous studies examining this topic still have inconsistent results. Seeing this, the researchers tried to re-examine using a sample of retail companies/trading sector, services and investment in the retail trade sub-sector listed on the Indonesia Stock Exchange (IDX) in 2015-2020. The sample of this research was taken through purposive sampling, totaling 20 companies. Data analysis methods are descriptive statistics, regression analysisi, and Moderated Regression Analysis (MRA) using Econometric Views (EViews) 10 for windows. The results showed that asymmetric information and liquidity had a positive effect on earnings management, while liquidity and leverage had a negative effect on earnings management. Independent commissioners can moderate the effect of asymmetric information and liquidity on earnings management but cannot moderate the effect of profitability and leverage on earnings management. The audit committee can moderate the effect of financial leverage (profitability, liquidity and leverage) on earnings management, but cannot moderate the effect of asymmetric information on earnings management.